Double Upper Lip - Tah, Ravindra; Sharma, S.N. (Indian Journal of Plastic Surgery, 1990)
Eleven case of double upper lip were seen by us during the last 10 years, of which 9 were males and 2 were females. The embryology, clinical appearance, histopathology and surgical correction of the deformity has been discussed with a review of the literature. A new technique, to enchance aesthetics of the lip, is being described.
Keywords: Lip; Double; Duplication; Congenital